Environmental survey of natural gamma background radiation dose rates in Rembau District, Malaysia / Ahmad Taufek Abdul Rahman, Abd. Khalik Wood and Amir Abd. Wahit - Abdul Rahman, Ahmad Taufek; Wood, Abd. Khalik; Abd. Wahit, Amir (2006)
Universiti Teknologi MARA Negeri Sembilan (UiTM NS) has conducted an environmental survey of natural background gamma radiation dose rates in Rembau district, Malaysia. The natural radiation sources have always existed on earth and all living organisms are continually exposed. The doses to human beings from natural radiation are important, because they contribute the largest component of equivalent dose received by the world population. About 74 % of area was carried out to map the distribution of terrestrial gamma radiation dose rates in Rembau district. The highest terrestrial gamma radiation dose rate measured is 857±14 nGy h-1. The lowest terrestrial gamma radiation dose rate measured is 114±14 nGy h-1. The average terrestrial gamma radiation dose rate measured in Rembau district is 383±18 nGy h- 1. These data are presented as terrestrial gamma radiation dose rates map of Rembau district, Malaysia. This map provides a usable regional picture of environmental gamma background radiation dose rates excluding cosmic radiation in Rembau district.